Filamen printer 3D berbasis limbah PET (polyethylene terephthalate) dan kitosan cangkang udang - Azami, I.; Kurniasih, P.; ., S.; Amantha, A.; Habiiburrahman, N.; Sari, N.H. (Dinamika Teknik Mesin, 2024)
One alternative for processing PET (polyethylene terephthalate) plastic waste is to convert it into a basic material for making 3D printer filaments with the addition of shrimp shell chitosan. The addition of shrimp shell chitosan to the filament can increase its mechanical strength. The aim of this research is to determine the best formulation and effectiveness of the combination of PET plastic with chitosan as 3D printer filament on the mechanical properties and microstructure of the surface. Making 3D printer filament from a combination of PET and shrimp shell chitosan using a double screw extruder with varying ratios between PET and shrimp shell chitosan (99 : 1, 97.5 : 2.5 and 95 : 5) with temperature variations at 175° C (Hopper Zone ), 195°C, 225°C, 245°C (Die zone) using a screw rotation speed of 50 rpm, with the testing process including a tensile test, to determine the mechanical properties of the material by analysis using the SEM (Scanning Electron Microscope) test ) to identify the surface morphology and size of the filament material. The test results for composition 99:1 (sample 1) had the lowest tensile strength value of 35.79 MPa, breaking 0.10 mm with an elongation value of 0.32%. Composition 97.5:2.5 (sample 2) with a tensile strength value of 96.20 Mpa, longest breaking length of 0.13 mm and highest elongation value of 0.42%. Composition 95:5 (sample 3) only has the highest tensile value of 98.95 MPa, with a breaking length of 0.06 mm and the lowest elongation of 0.18%.